The Rupture Process and Location of the 2003 Zemmouri–Boumerdes Earthquake (Mw 6.8) Inferred from Seismic and Geodetic Data - Santos, Ruben (2015)
Abstract—This work is a study of the earthquake (Mw 6.8) that occurred on May 21, 2003 in Zemmouri–Boumerdes (Algeria) using methodology based on teleseismic data, uplift measurements, and synthetic aperture radar data. As a starting point, we fix the two source fault models obtained in this work (Solution 1: strike = 64 , dip = 50 , and rake = 97 ; Solution 2: strike 256 , dip 40 , and rake = 91 ) with a length of 60 km and width of 20 km to calculate the slip distribution that best explains the seismic and geodetic observations. The interferometric fringes revealed a strong displacement in the satellite direction (*53 cm) along the coast of Algeria between the cities of Boumerdes and Zemmouri. The inversion of teleseismic body waves for the two focal solution types (one plane dipping to the SE and the second plane dipping to the NW) showed distinct ruptures. However, both bilateral ruptures included two asperities, one near the hypocentre and the other at a shallower location. The maximum slip (Solution 1 = 3.8 m and Solution 2 = 4.0 m) occurred near the hypocentre in both seismic source models. The surface displacement model was obtained with Okada’s equations using the EDCMP algorithm. The three components of the displacements calculated were projected regarding the satellite direction (LOS—line-of-sight) for comparison with the interferogram. The geographic location of the fault plane was determined by comparing the uplift measurements with the vertical displacement models calculated with the source at several locations. The surface displacements calculated from these source models indicate that the model based on the SE plane and the epicentre location at 36.846 N and 3.660 E produces results closer to the interferogram and the uplift measurements.